(untitled) (Revista Lusófona de Educação, 2023)
Promoting equity has been and still is a fundamental challenge for educational systems around the world. While PISA has a stated goal of sharing information and guidance to shape national policies for achieving greater socio-economic equity, its actual role and the outcomes of the program are subject to much debate. This paper presents a scoping review of the available literature that focuses on the relationship between PISA implementation and (socio-economic educational) equity change. This review is twofold, including both (i) quantitative research aimed at gauging changes in equity indicators using PISA datasets, as well as (ii) qualitative research that discusses PISA’s impact on educational equity. Major databases were systematically searched, yielding 1180 hits. After independent assessment by different judges, a total of 51 articles met the criteria for inclusion, 27 of which qualitative and 34 quantitative. Analysis of the qualitative and quantitative literature is presented separately, both in tabular and narrative form, allowing the assessment of the amount, nature, and scope of the available literature and related gaps. Keywords: PISA; Equity; Scoping review; SES; Literature review.